The Relationship Between Fluid Intake Compliance with The Occurrence of Hypervolemia in Chronic Rentalfailure Patients Undergoing Hemodialysis at Grandmed Hospital Lubuk Pakam - Syara, Arfah May; Fridayanti, Sri (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Chronic kidney failure is irreversible damage to kidney function that requires kidney replacement therapy. Failure during hemodialysis therapy often occurs due to non-compliance. Actions taken for hemodialysis patients are regarding fluid intake. Compliance with limiting fluid intake is a key factor in determining the health level of hemodialysis patients. The research method used was cross sectional. The population were all chronic kidney failure patients in the Hemodialysis Room at Grandmed Lubuk Pakam Hospital with a total sample of 40 people taken using the purposive sampling method. The results showed that as many as 20 respondents or 50.0% were in the category of less compliant with limiting fluid intake. On the other hand, it showed that as many as 22 respondents or 55% experienced mild hyperlovemia. The results of statistical tests show that there is a relationship between compliance with fluid intake and the occurrence of hypervolemia in chronic kidney failure patients undergoing hemodialysis at Grandmed Lubuk Pakam Hospital in 2023 with a p-value of 0.000. If the patient is increasingly disobedient in limiting fluid intake in the body, the greater the fluid accumulation or hypervolemia will occur.